2021
DOI: 10.1186/s12935-021-02092-7
|View full text |Cite
|
Sign up to set email alerts
|

miR-198 inhibits the progression of renal cell carcinoma by targeting BIRC5

Abstract: Background miR-198 is involved in the formation, migration, invasion, and metastasis of various malignant cancers. However, the function and mechanism of action of miR-198 in the tumorigenesis of renal cell carcinoma (RCC) remain elusive. Here, we aimed to explore the role of miR198 in RCC. Methods Immunohistochemistry was performed to estimate the level of survivin in RCC sections. Quantitative real-time polymerase chain reaction was performed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Total RNA was extracted from the cells using the TRIzol kit (Takara, Dalian, China) as described previously (18). 1 mg RNA was used to transcribe cDNA using the HiScript II Q RT SuperMix (R223-01, Vazyme).…”
Section: Qrt-pcr Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNA was extracted from the cells using the TRIzol kit (Takara, Dalian, China) as described previously (18). 1 mg RNA was used to transcribe cDNA using the HiScript II Q RT SuperMix (R223-01, Vazyme).…”
Section: Qrt-pcr Assaymentioning
confidence: 99%
“…Cell counting kit-8 (CCK-8) assay (Beyotime) was performed to evaluate the U251cell viability as before (18). Briefly, 1x10 5 U251cells were seeded in a 96-well plate (NEST, China) for 24 h, and then treated with different concentrations of TPL for another 24h.…”
Section: Cck8 Assaymentioning
confidence: 99%
“…[16] miRNA is another form of ncRNAs, which plays a major role in many malignant behaviors of human tumors. [17,18] As a tumor suppressor, miR-198 has been found to be less expressed in some tumors, such as renal cell carcinoma (RCC), [19] CRC, [20] osteosarcoma (OS), [21] and GC. [22] Of course, miR-198 is downregulated in OC tissues.…”
Section: Introductionmentioning
confidence: 99%
“…These data indicate that miR-198 has therapeutic potential for PC. miR-198 has been shown to have a potent tumor-suppressor function in other types of cancers including renal cell carcinoma, ovarian cancer, lung cancer, and prostate cancer [ 59 , 60 , 61 , 62 ]. Furthermore, many studies have demonstrated that miR-520h could significantly inhibit tumor progression or prevent chemotherapy drug resistance in different types of cancers such as PC, multiple myeloma, and gastric cancer [ 63 , 64 , 65 ].…”
Section: Introductionmentioning
confidence: 99%